PEMANFAATAN EKSTRAK BIJI Barringtonia asiatica L. UNTUK PENGENDALIAN KEONG MAS PADA TANAMAN PADI DI DESA POPONTOLEN KECAMATAN TUMPAAN KABUPATEN MINAHASA SELATAN - MARGONO .; Jusuf Manueke; Juliet M.E. Mamahit; Caroulus S. Rante (COCOS, 2014)
ABSTRACTMargono. Use of seed extract Barringtonia asiatica L. to control golden snail in rice plants at village Popontolen, subdistrict Tumpaan, district Minahasa Selatan. Under Guidence Dr Ir Jusuf Manueke, MP as chaiman, Dr. Ir. Juliet M.E. Mamahit, M.Si and Ir. Caroulus S. Rante, MS as member.The study aimed to determine the effect of seed extract Bitung , B. asiatica against golden snail mortality. The experiment was conducted in the village of popontolen, subdistrict Tumpaan, Minahasa Selatan Regency. The duration of less than six months of the study, which lasted from August 2013 until January 2014. Research using experimental methods with Complete Randomized Design (CRD) consisting of four treatments and three replications. The treatment used is the concentration of seed extract Bitung 0% (control), 10%, 20% and 30%. Observations death snails performed 6, 12, 24, 30, 42, 54 and 66 hours after application.Symptoms begin with snails death marked the release of mucus from the surface of the body and the body slowly over time regardless of the shells. The observation of 6 hours after the application has been found dead snails in the treatment of Bitung seed extract with a concentration of 20 % and 30 % , ie respectively 14.31% and 28.23%. In observation 12 hours after application, the third seed extract concentration and Bitung (10%, 20% and 30%) had deadly snails above 80.00%. Therefore the use of seed extract B. asiatica with a concentration of 10% can already be used to control snails in rice plants.Keywords: Barringtonia asiatica, golden snail, Minahasa Selatan